The adaptation of students during academic mobility processes: The case of Belarus - Laputsky, Victor (Eastern Review, 2019)
The article describes the experience of Belarus in the field of international academic mobility. The purpose of the article is to reveal the theoretical and methodological aspects of the internationalization of higher education and academic mobility and describe the current situation on the integration of Belarus into the international context, from a sociological and statistical perspective. In view of the significant number of Belarusian students in Polish and Eastern European universities, the topic is relevant in the context of the study of academic mobility in Eastern Europe. As part of the first task, the theoretical aspects of studying the internationalization of higher education in the country are described – with justification for the development of both the external and internal internationalization, as well as a description of various types of students’ adaptation when studying abroad (academic, linguistic, socio-cultural). As part of the second task, the results of the author’s sociological study are presented, which includes two main components. Firstly, the results of a survey devoted to the study of the views of Belarusian students regarding academic mobility (including cognitive, affective and behavioural aspects) are presented. Secondly, the results of a series of in-depth interviews among participants in the processes of academic mobility aimed at studying the practices of Belarusian students staying abroad for educational purposes are considered. The studies showed the need to increase the awareness of Belarusian students about the possibilities of academic mobility (the vast majority of students have incomplete or fragmented ideas about the possibilities of academic mobility), as well as the problem of the incomplete involvement of the Belarusian higher education system in the international context (the activity of students participating in exchange programs is not counted at Belarusian universities). In accordance with the results, recommendations are given for the further integration of the Belarusian higher education system into the international context.